ARTERIAL STIFFNESS, CENTRAL BLOOD PRESSURE, AND CARDIAC BIOMARKERS ANALYSIS DURING LONG-TERM WALKERS. (June 2018) - Vitorino, P.; Sousa, W.; Euzebio, M.; Sousa, A. L.; Jardim, T.; Jardim, P.C.; Barroso, W. Sebba
Abstract : Objective: To evaluate arterial stiffness, central arterial pressure and to correlate them with cardiac biomarkers in long-term walkers. Design and method: Longitudinal prospective study with participants of the Ecological Walk of Goiás. Evaluated the peripheral systolic blood pressure (SBPp), peripheral diastolic (DBPp), central systolic blood pressure (SBPc), central diastolic blood pressure (DBPc), pulse wave velocity (PWV), augmentation index (Aix) and peripheral vascular resistance (PVR) using the Mobil O'Graph® device. The evaluation was performed 30 days before the event (A0) and at the end of the 1st (A1), 2nd (A2), 3rd (A3) and 4th (A4) day of the walk. Used Anova of repeated measures, post hoc of Bonferroni and the tests of Pearson or Spearman. Results: 25 men with mean of 46 ± 10.5 years and mean BMI of 20.2 ± 2.3 kg/m2. There was a reduction of the SBPp from the A0 (122.8 ± 2.2) to A1 (111.6 ± 2.1) (p = 0.004) and SBPc from A0 (110.2 ± 2.2) to A1 (101 ± 1.8) (p = 0.035). The CK-MB enzyme correlated with PVR in both A1 (r = 0.445, p < 0.033) and A4 (r = 0.554, p < 0.006). Troponin T showed correlation in A4 with SBPc (r = 0.468, p < 0.024) and SBPp (r = 0.470, p < 0.023). Conclusions: Central and peripheral systolic blood pressure decreased between the initial evaluation and the first day. There was no correlation between arterial stiffness parameters and cardiac biomarkers. There was a positive correlation between CK-MB and peripheral vascular resistance on the first and fourth day as well as between troponin T and central systolic blood pressure on the fourth day.